Antonio Gramsci: la letteratura per l'infanzia tra radici culturali-popolari e educazione - Chiara Lepri (Firenze University Press, 2019)
The paper intends to offer an in-depth analysis of Antonio Gramsci's contribution to the reflection on children's literature, whose non existence, in the years in which the intellectual writes the Quaderni from the fascist prison, leads to a "nexus of problems" concerning the lack of a national popular Italian literature. There are many suggestions that rose through the interest shown by Gramsci, on various fronts, towards children's literature: from the 'public' Gramsci of the Quaderni to the 'private' Gramsci of the Lettere, from the affirmation of the need for literary enjoyment of the people to the exemplary exercise of a 'living paternity', we not only grasp an example of method, but also a militant pedagogical commitment to the people/childhood world expressed with extraordinary clarity, rigor, sensitivity, yet to be investigated to rediscover its richness and actuality.